Unusual Clinical Presentation of Cutaneous Angiosarcoma Masquerading as Eczema: A Case Report and Review of the Literature. (7th October 2013) - Trinh, Nhat Q.; Rashed, Issra; Hutchens, Kelli A.; Go, Aileen; Melian, Edward; Tung, Rebecca
Abstract : An unusual case of cutaneous angiosarcoma clinically mimicking eczema is described. A 98-year-old Caucasian male presented with a 6-month history of a flesh-colored, subcutaneous nodule on his left forehead with contralateral facial erythema and scaling that had been previously diagnosed as eczema. Despite treatments with topical steroids and moisturizers, the condition did not resolve. At our clinic, excisional biopsy of the forehead lesion and scouting biopsies from the contralateral cheek were performed which revealed cutaneous angiosarcoma. The described case illustrates that dermatitis-like features should be considered as a rare clinical manifestation of cutaneous angiosarcoma. It also demonstrates that these lesions may respond well to radiotherapy as a single modality.